Kommunens namn i kommunsloganer: perspektiv från lingvistik och marknadsföring - Ainiala Terhi; Sjöblom Paula; Hakala Ulla (Kungl. Gustav Adolfs Akademien för svensk folkkultur, 2022)
Most municipalities in Finland have a slogan. At best, the slogan stems from the municipality’s strategy and thereby conveys the mission of the municipality and strengthens both its image and its memorability. In our interdisciplinary project, we are analysing municipal slogans from both a linguistic and a marketing point of view, exploring their ability to promote the municipality’s reputation and visibility. Our analysis here is limited to slogans that include the name of the municipality; in these cases, the different linguistic ways in which the name of the municipality can function as a motivation are explored. The focus is on the syntactic position of the name and its discursive function, as well as on alliteration with the name in the slogans. Based on this linguistic analysis, the motivation for such slogans in municipalities’ marketing discourse is considered